Kill bill. Volume 1 [videorecording (Blu-Ray + DVD)] - Tarantino, Quentin; Thurman, Uma; Fox, Vivica A., 1964-; Carradine, David (Lionsgate, 2023)
A pregnant woman is critically injured on her wedding day by her former boss and cohorts, who are assassins. She goes into a coma that lasts for four years, and when she wakes up she is ready for revenge.